Histoplasmosis: diagnostic and therapeutic aspect - Wijaya, Meiliyana; Adawiyah, Robiatul; Wahyuningsih, Retno (Indonesian Journal of Tropical and Infectious Disease, 2021)
Histoplasmosis has been reported since 1932 in various regions in Indonesia. This disease is caused by thermally dimorphic fungus Histoplasma capsulatum var. capsulatum which is experiencing an increasing incidence worldwide. Human infection occurs when spores in soil contaminated with bird and bat droppings are inhaled and change to form yeast in the lungs. The majority of these forms of infection are mild and can heal on their own, but if large numbers of spores/ inoculum are inhaled, or the host is immunosuppressed, serious lung disease and even dissemination may occur with a high mortality rate. The diagnosis can be made by combining clinical symptoms with laboratory test results. Conventional laboratory methods such as direct examination or histopathology and culture are the gold standards for histoplasmosis diagnosis. The weakness of culture is the nature of H. capsulatum as a slow grower fungus that takes 4-6 weeks to grow. In addition, laboratory tests can be carried out with antibody detection or antigen detection. Antigen detection is more beneï¬ cial for hosts with immunosuppression or acute form, while antibody detection is more important in the chronic form of the diseases. Molecular-based assays have high speciï¬ city but are not yet available commercially and are more widely used for culture identiï¬ cation to conï¬ rm the species of H. capsulatum. Histoplasmosis therapy usually begins with the administration of amphotericin B for around two weeks, followed by maintenance with itraconazole for 6 - 9 months duration. A careful history of possible exposure and the appropriate laboratory diagnostic approach is essential to provide appropriate therapy.